Molecular delineation of de novo small supernumerary marker chromosomes in prenatal diagnosis, a retrospective study - Shuang Hu; Xiangdong Kong (Elsevier, 2023)
Objectives: To define the genotype-phenotype correlation of small supernumerary marker chromosomes (sSMCs) and conduct precise genetic counseling, we retrospectively searched and reviewed de novo sSMCs cases detected during prenatal diagnosis at The First Affiliated Hospital of Zhengzhou University. Materials and methods: Chromosome karyotypes of 20,314 cases of amniotic fluid from pregnant women were performed. For 16 samples with de novo sSMCs, 10 were subjected to single-nucleotide polymorphism (SNP) array or low-coverage massively parallel copy number variation sequencing (CNV-seq) analysis. Results: Among the 10 sSMCs cases, two sSMCs derived from chromosome 9, and three sSMCs derived from chromosomes 12, 18 and 22. The remaining 5 cases were not identified by SNP array or CNV-seq because they lacked euchromatin or had a low proportion of mosaicism. Four of them with a karyotype of 47,XN,+mar presented normal molecular cytogenetic results (seq[hg19] 46,XN), and the remaining patient with a karyotype of 46,XN,+mar presented with Turner syndrome (seq[hg19] 45,X). Five sSMCs samples were mosaics of all 16 cases. Conclusion: Considering the variable origins of sSMCs, further genetic testing of sSMCs should be performed by SNP array or CNV-seq. Detailed molecular characterization would allow precise genetic counseling for prenatal diagnosis.